ANOTHER LOST ARCADIA? CARLOS GERMÁN BELLJ'S POETRY, BETWEEN UTOPIA AND BOREDOM. NOTES ON ¡CIBERNETIC FAIRY! - Silva Peralta, Allan (2006)
Thanks to a neat aesthetic proposal, Belli 's poetry has reached itshighest peaks. The article, through careful reading of "Oh, CiberneticFairy", profits from former critics to his work and finds new meanings inBelli' s poetic world.